In Silico And In Vivo Analysis Of Otu Deubiquitinases Otub1, Otub2 And Otulin Protein-protein Interactions - Zulkifli, Nur Wahida (2023)
In this post-genomic era, proteomic and interactomic data are important sources for understanding the molecular basis of cell functional diversity. Research in these fields is still progressing, with at least 90% of proteins annotated so far and many more interactions to be uncovered to complete the proteome and interactome maps. The purpose of this study is to contribute to the expansion of human interactome data by focusing on the deubiquitinating enzymes (DUBs) protein-protein interaction (PPI) using several in silico and in vivo approaches. First, a DUBs interactome was built on Cytoscape ver 3.9.1 using data from IMEx database and analysed using various graph theory algorithms. The DUBs interactome consisted of 3,406 nodes and 4,982 edges, whereas a cancer protein subnetwork extracted from the interactome revealed that DUBs are significant in cancer biology. Concluding the interactome study, OTUB1, one of the proteins with strong network characteristics, along with its closest homologue OTUB2, and the newest family member OTULIN, were selected for yeast two-hybrid (Y2H) screening against human cDNA library derived from HEK293. Y2H bait and cDNA library prey vectors were generated using Gateway technology, first in donor vector TOPO/pDONR222 before being shuffled into destination vector pDEST32/22. The bait vector is sequence-verified, and the prey vector is of sufficient quality and quantity to represent human cDNA with total clones of 6.8×106 cfu. Both vectors were transformed into MaV203 S. cerevisiae strain for Y2H screening to identify putative interacting proteins